Effect of dates of planting on growth, yield and quality of ginger (Zingiber officinale Roscoe) - P M Haldankar, R N Nawale, A R Yadav, R G Khandekar, G N Korake, (Journal of Spices and Aromatic Crops, 2014)
The trial was carried out during 2008–09 to study the ideal date of planting and spacing to obtain better growth, yield and quality of ginger crop var. ‘IISR Mahima’. The experiment was laid out in Split Plot Design with dates of planting as main plot treatment (15th April, 1st May, 15th May, 30th May and 15th June) and three treatments of spacing as sub plot treatment (35 cm × 25 cm, 25 cm × 25 cm and 15 cm × 25 cm) with three replications. The observations were recorded on dry recovery (%), harvest index, oil and crude fibre content. Dates of planting had significant effect on all the characters studied. April 15th planting showed better oil content. Among spacings, the spacing of 35 cm × 25 cm gave highest dry recovery. The closer spacing of 15 cm × 25 cm recorded higher harvest index. It was observed that spacing had no significant effect on quality attributes viz., oil and crude fibre content. The treatment combination of 15th April planting and 35 cm × 25 cm spacing exhibited higher dry recovery. The treatment combination of 15th April planting and 15 cm × 25 cm spacing showed maximum harvest index. Economics of interactions revealed maximum net returns of Rs. 559,690.1 ha-1 with benefit cost (B:C) ratio of 2.67 for the treatment combination of 15th April planting and 15 cm × 25 cm spacing.